DNA Barcoding Diatoms From China With Multiple Genes - Zou, Shanmei; Bao, Yachao; Wu, Xuemin; Wang, Changhai (Frontiers in Marine Science, 2021)
Diatoms play a key role in water quality assessments and algae bloom. However, taxonomic confusion often exists for diatoms while morphological characters are extremely diverse for species identification. DNA barcoding with multiple genetic markers can contribute much to diatom diversity investigation. In this study, we employed sequences of four genetic markers (COI, rbcL, SSU and LSU) for discriminating the diatom strains from both marine and freshwater environments of China, by tree, distance and character-based barcoding methods. The available published diatom sequences were also incorporated to our new sequences. A total of 93 rbcL, 81 COI, 83 SSU and 75 LSU sequences of diatom samples were obtained in this study. The multiple genetic markers discriminated most species clearly. The species identification by micrographic observation was generally consistent with the DNA barcoding analysis except that some potential cryptic species were revealed by DNA barcoding. The COI, rbcL and LSU all showed high taxonomic resolution in species level by phylogenetic and character-based analysis. Some potential identification errors in public diatom sequences were also found. The phylogenetic and character-based analysis revealed consistent species identification, and showed clearer species discrimination than distance-based method. In conclusion, our study gave a comprehensive diatom identification, and complemented many diatom reference sequences to public databases.